2021
DOI: 10.1016/j.celrep.2021.109242
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal figure-ground responses in primate primary auditory cortex

Abstract: Highlights d Neuronal figure-ground modulation in primary auditory cortex d A rate code is used to signal the presence of auditory figures d Anteriorly located recording sites encode perceptual saliency d Figure-ground modulation is present without perceptual detection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Tone-cloud stimuli similar to the sounds employed in this study have been used with functional MRI, MEG, and electroencephalography to probe auditory figure–ground segregation in typical adults. These studies showed that although evidence of temporal coherence processing is measurable in the auditory cortex, attention can significantly enhance the neural representation of the foreground figure, especially in later parietal regions [ 32 , 34 , 56 , 57 ]. Indeed, animal models show that temporal coherence sensitivity and neural computations that support auditory scene analysis begin subcortically, as early as the cochlear nucleus [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tone-cloud stimuli similar to the sounds employed in this study have been used with functional MRI, MEG, and electroencephalography to probe auditory figure–ground segregation in typical adults. These studies showed that although evidence of temporal coherence processing is measurable in the auditory cortex, attention can significantly enhance the neural representation of the foreground figure, especially in later parietal regions [ 32 , 34 , 56 , 57 ]. Indeed, animal models show that temporal coherence sensitivity and neural computations that support auditory scene analysis begin subcortically, as early as the cochlear nucleus [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…For auditory stimuli, figure-ground perception is not exclusive to humans; it has also been observed in animals, in studies on figure-ground processes investigated through noise and sound. Extracellular recordings demonstrated increased multiunit activities in the auditory area 57 . Further, auditory areas have been the focus of previous human studies on stream segregation through selective attention and figure-ground segregation 46,47,49,51 .…”
Section: Discussionmentioning
confidence: 98%
“…The model allows systematic neurophysiology in a way that would never be possible in humans. Recordings of multiunit activity demonstrate tonic responses to figure onset that are present in all three auditory core areas in the superior temporal plane ( Schneider et al, 2021 ). We can also carry out fMRI in the macaque to measure BOLD activity in neuronal ensembles: this allows a direct comparison with human studies.…”
Section: Brain Mechanisms For Auditory Cognition Relevant To Speech-i...mentioning
confidence: 99%